Penerapan Terapi Musik Instrumental Melalui Senam Terhadap Lansia Penderita Hipertensi di Panti Werdha Elim Kota Semarang - Ani Alfiyani; Fadly Husain (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
Panti Werdha Elim is an institution dedicated to elderly care that not only provides services but also recognizes the rights and responsibilities of the elderly. The main task of Panti Werdha Elim is to ensure the fulfillment of the elderly's needs, both in terms of physical and psychological care. One of the most common diseases suffered by the elderly is hypertension. Hypertension is a condition where a person's blood pressure is high and poses a risk of serious health problems. Panti Werdha Elim provides health care facilities in the form of music therapy for the elderly. This research aims to determine the application of music therapy in the elderly and to assess the effectiveness produced after the therapy is conducted. This research uses a descriptive qualitative approach by collecting data through field observations, interviews, and literature studies. The main informants consist of nurses, therapists, and the elderly. The results of this study indicate that therapy is carried out for 15-30 minutes using music provided by the institution. In addition, the effectiveness produced is that the elderly feel a significant change in their health condition when this therapy is performed regularly. Another finding is that therapy is not only conducted in groups but also includes individual therapy for clients in need. Therefore, this research provides a detailed overview of the music therapy conducted and the dynamics of the social conditions of the elderly at Panti Werdha Elim.